Proposal for the assessment to quantitative dermal exposure limits in occupational environments: Part 2. Feasibility study for application in an exposure scenario for MDA by two different dermal exposure sampling methods - Brouwer, D. H. (BMJ Group, 1998)
OBJECTIVE: To evaluate two different techniques for assessing dermal exposure to 4,4'-methylene dianiline (MDA) in a field study. The results were used to test the applicability of a recently proposed quantitative dermal occupational exposure limit (DOEL) for MDA in a workplace scenario. METHODS: For two consecutive weeks six workers were monitored for exposure to MDA in a factory that made glass fibre reinforced resin pipes. Dermal exposure of the hands and forearms was assessed during week 1 by a surrogate skin technique (cotton monitoring gloves) and during week 2 by a removal technique (hand wash). As well as the dermal exposure sampling, biological monitoring, measurement of MDA excretion in urine over 24 hours, occurred during week 2. Surface contamination of the workplace and equipment was monitored qualitatively by colorimetric wipe samples. RESULTS AND CONCLUSIONS: Geometric means of daily exposure ranged from 81-1762 micrograms MDA for glove monitoring and from 84-1783 micrograms MDA for hand washes. No significant differences, except for one worker, were found between exposure of the hands in weeks 1 and 2. Significant differences between the mean daily exposure of the hands (for both weeks and sampling methods) were found for all workers. The results of the colorimetric wipe samples indicated a general contamination of the workplace and equipment. Excretion of MDA in 24 hour urine samples ranged from 8 to 249 micrograms MDA, whereas cumulative MDA excretion over a week ranged from 82 to 717 micrograms MDA. Cumulative hand wash and MDA excretion results over a week showed a high correlation (R2 = 0.94). The highest actual daily dermal exposure found seemed to be about 4 mg (hand wash worker A on day 4), about 25% of the external DOEL. Testing of compliance by means of a biological limit value (BLV) led to similar results for the same worker. It is concluded that both dermal exposure monitoring methods were applicable and showed a compatible performance in the present exposure scenario, where the exposure relevant to dermal absorption is considered mainly restricted to hands. The concept for a DOEL seemed to be relevant and applicable for compliance testing and health surveillance in the situation under investigation.